Upaya Penegakan Hukum Melalui Sidak BPOM Padang Guna Mewujudkan Perlindungan Konsumen Terhadap Peredaran Produk Makanan Kadaluarsa - Widya Yoseva (Journal of Global Legal Review, 2024)
Law enforcement against the circulation of expired goods is a crucial step in consumer protection. The Food and Drug Supervisory Agency (BPOM) Padang plays a significant role in conducting surprise inspections (sidak) to ensure the safety of products circulating in the market. This study aims to examine law enforcement efforts through BPOM's Padang sidak in realizing consumer protection against the circulation of expired goods. The research method used is a case study by analyzing secondary data in the form of BPOM's Padang sidak reports on supermarkets and convenience stores suspected of selling expired goods. The results show that BPOM's Padang sidak is effective in identifying and securing expired goods from circulation. Furthermore, sidak also has a deterrent effect on businesses that do not comply with regulations. However, some challenges are still found in the implementation of BPOM's Padang sidak, such as limited resources and coordination among related agencies. Therefore, further steps are needed to improve the effectiveness of BPOM's padang sidak, such as enhancing coordination among agencies, increasing BPOM's Padang human resource capacity, and raising consumer awareness of their rights to safe and quality products. Thus, consumer protection against the circulation of expired goods can be more optimal.